Biotechnical monitoring system for determining person's health state in polluted environment using hybrid decisive rules. (29th August 2019) - Al-Kasasbeh, Riad Taha; Korenevskiy, Nikolay; Filist, Sergey; Shatalova, Olga Vladimirovna; Alshamasin, Mahdi Salman; Shaqadan, Ashraf Adel
Setting exposure criteria to environmental pollutants is dependent on a range of interrelated variables, therefore it is complicated to understand and model exposure levels. Fuzzy logic is a convenient approach to integrate expert judgment and mathematical modelling in one predication model. Monitoring health state of population is useful tool to develop and calibrate parameters of fuzzy logic model. Analysis of the indistinct decisive rules making a basis of creation of knowledge bases of expert systems, solving problems of monitoring of a state of environment and health of humans on the basis of collectives of the hybrid mathematical models working with diverse structure of data in the absence of their exact analytical description are considered. Disease risk was analysed for populations living in two environmental conditions, one a polluted mining community (Zheleznogorsk city) and the other a cleaner environment community (Kursk city). Diseases screening for polluted area was conducted and analysed.